Dual‐Responsive Soft Actuators with Integrated Sensing Function Based on 1T‐MoS2 Composite. (22nd July 2021) - Ji, Qixiao; Jing, Zhuang; Shen, Jinjie; Hu, Ying; Chang, Longfei; Lu, Luhua; Liu, Muye; Liu, Jiaqin; Wu, Yucheng
Abstract : Soft Actuators An intelligent soft gripper with self‐sensing function based on 1T MoS2 and carbon nanotubes composite actuator is fabricated by Ying Hu, Longfei Chang, Luhua Lu, and co‐workers in article number 2000240 . This gripper can not only deform to grasp objects under light stimulation, but also realize the integrated sensing of its own light‐driven manipulation process.